Governance Asymmetry Under Economic Pressure: A Resource-Based Perspective on K-Shaped Sustainability in Indonesia - Satyaguna, I Made; Cahyono, Dwi (Journal of Applied Business, Taxation and Economics Research, 2026)
When developing countries face economic problems, the recovery often occurs unevenly across sectors and social classes. Indonesia is currently facing various structural difficulties, such as a shrinking middle class, increasing informal employment, rising taxes, changes in capital flows, and symptoms of deindustrialization. This situation can have an impact on the long-term health of the economy. This study aims to examine the ability of governance to influence sustainability trends in the context of economic pressures through the perspective of Resource-Based View (RBV). Using a conceptual-analytical approach based on macroeconomic secondary data from 2019 to 2025, this study shows that variations in sectoral and social group resilience are influenced by governance capabilities that serve as strategic resources at the national level. Governance asymmetry has led to a K-shaped pattern of sustainability, with some sectors showing adaptive resilience and others showing structural fragility. This research underscores the importance of policy coordination, implementation of structural adjustments, and strengthening of social protection systems to eliminate governance asymmetry and promote sustainable growth in a more open Indonesia.